Function from configurational degeneracy in disordered framework materials - Reynolds, Emily M.; Wolpert, Emma H.; Overy, Alistair R.; Mizzi, Luke; Simonov, Arkadiy; Grima, Joseph N.; Kaskel, Stefan; Goodwin, Andrew L. (Faraday Discussions, 2021)
The existence of correlated disorder in molecular frameworks is an obvious mechanism by which unusual cooperative phenomena might be realised. We show that the use of local-symmetry lowering approaches can allow ostensibly high-symmetry framework structures to harbour exotic disordered states often studied in the context of spin lattice models. These states exhibit strongly cooperative behaviour that might be exploited in anomalous mechanical, host/guest, and information storage behaviour. Our contribution focuses in particular on the concepts of (i) combinatorial mechanics, (ii) adaptive flexibility, and (iii) error-correcting data storage in framework materials.
CRIS-Team Scopus Importer:2022-04-14